Normality and homoscedasticity of stock market returns: the case of Malaysian and some major stock markets - Othman Yong, (Penerbit Universiti Kebangsaan Malaysia, 1990)
Many prior studies regarding the behavior of stock prices have shown that the stock prices are not normally distributed. Some offer stable Paretian to be the distribution, while some others offer the mixture of normals distribution. In this study of Malaysian and five major stock markets, it is shown that stock prices (as reperesented by indices) do exhibit normal distributions, but within short time spans. Longer time spans result in stock prices behave not according to normal distribution. In addition, the differing variances found between periods, indicate that the variances are not constant over time. In conclusion, the results of this study support the hypothesis that stock price movements are mixtures of normals with differing variances as proposed by Hall, Brorsen, and Irwin (1989) in their study regarding the behavior of futures prices.